Design of a Weight-Optimized Gearbox for a Formula Student Car - Alexsson, Emil; Henrikson, Erik; Lund, Carl; Tsobanoglou, Christian (My University, 2021)
Chalmers Formula Student is a team consisting of student engineers that design and build race cars to compete against other universities’ teams. Since 2019, Chalmers Formula Student has been designing electric powered four-wheel drive cars. In 2020, Chalmers Formula Student began utilizing electric machines and gearboxes powering all wheels at the wheel hub. This design has many advantages in terms of mechanical packaging and lowering the center of gravity, but the design also means higher mass for the shock absorbers to handle, also called unsprung mass. Higher unsprung mass has a negative effect on the vehicle dynamics. The project purpose is therefore to design a lighter gearbox than the most recently manufactured Chalmers Formula Student gearbox to reduce the unsprung mass. This report covers the process of developing a gearbox for the Formula Student car with the purpose previously mentioned. The project starts with investigating different gearbox configurations via a concept generation, resulting in that a single stage planetary gearbox is the most suitable concept. Then a method for deriving the dimensioning load cases for the gears, bearings and gearbox housing is developed by translating sensor data from competition to resulting forces. The load cases are then used for dimensioning the gears with the gear dimensioning software KISSsoft and for stress and deformation analysis on the gearbox housing and bearings with the FEM software ANSYS and 3D-modelling software CATIA V5. The result is a single stage planetary gearbox with a gear ratio of 11.5:1 that is 2.4% lighter than the most recent manufactured Chalmers Formula Student gearbox. However, if only the shared components are compared the final design is 12.3% heavier. The high gear ratio resulted in problematic gear design resulting in heavy gears in order to achieve acceptable safety factors. The conclusion is that even though the developed gearbox became marginally lighter, a single stage planetary gearbox is not a suitable gearbox layout for the application. However, the methods for developing the dimensioning load cases are considered accurate and suitable for dimensioning future gearboxes.
Keywords: Gearbox; Formula Student; Gears; Planetary gearbox; Unsprung mass; Design; Dynamics